Volatility Expectations and Returns - LOCHSTOER, LARS A.; MUIR, TYLER (Journal of Finance, 2022)
ABSTRACT We provide evidence that agents have slow‐moving beliefs about stock market volatility that lead to initial underreaction to volatility shocks followed by delayed overreaction. These dynamics are mirrored in the VIX and variance risk premiums, which reflect investor expectations about volatility, and are also supported in both surveys and firm‐level option prices. We embed these expectations into an asset pricing model and find that the model can account for a number of stylized facts about market returns and return volatility that are difficult to reconcile, including a weak or even negative risk‐return trade‐off.